Diaphragmatic rupture denervation. - Croci, Fabio; Bounous, Mario; Gastambide, Carmelo; Ruiz Liard, Alfredo (Cirugía del Uruguay, 1984)
Authors describe a secondary diaphragmatic rupture in close traumatism, in a multiple trauma palien!, with special and no! very. frequent anatomo-pathological and clinical characteristics. The case was diagnosed only on !he fifth day in spite of previous laparotomy. Treatmeant required thoracic implantation of a prosthesis. Subsequent evolution was good.